2021
DOI: 10.1128/msphere.01255-20
|View full text |Cite
|
Sign up to set email alerts
|

The Majority of Typhoid Toxin-Positive Salmonella Serovars Encode ArtB, an Alternate Binding Subunit

Abstract: Salmonella enterica encodes a wide array of virulence factors. One novel virulence factor, an A2B5 toxin known as the typhoid toxin (TT), was recently identified among a variety of S. enterica serovars. While past studies have shown that some serovars encode both the TT (active subunits CdtB and PltA and binding subunit PltB) and a second binding subunit (ArtB), these serovars were thought to be the exception. Here, we show that genes encoding the TT are detected in more than 100 serovars representing distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 67 publications
(104 reference statements)
2
23
0
Order By: Relevance
“…diarizonae in this study. This finding is in accordance with the study by Gaballa et al (2021), who revealed the presence of cdtB in S. enterica subsp. enterica, S. enterica subsp.…”
Section: Discussionsupporting
confidence: 94%
“…diarizonae in this study. This finding is in accordance with the study by Gaballa et al (2021), who revealed the presence of cdtB in S. enterica subsp. enterica, S. enterica subsp.…”
Section: Discussionsupporting
confidence: 94%
“…A similar situation has been reported in S . Javiana ( 26 , 27 ). pltC is found at a genomic locus that is distant from all other typhoid toxin-related genes, where it resides immediately downstream of an ADP-ribosyltransferase pseudogene, sty1362 ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…artB is also present on typhoidal Salmonella serovars and is associated with an artA pseudogene that is likely not expressed. Recently S. Typhi artB has been found to be present on many additional Salmonella serovars and may provide an alternative binding subunit for Typhi Toxin (TT) [28]. artB of S. Typhi was also determined to be expressed, especially under conditions that may occur inside of host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently S . Typhi art B has been found to be present on many additional Salmonella serovars and may provide an alternative binding subunit for Typhi Toxin (TT) [ 28 ]. art B of S .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation